2005
DOI: 10.1007/s10443-005-1130-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Energy Absorption in Syntactic Foams by Nanoclay Incorporation for Sandwich Core Applications

Abstract: Syntactic foams are closed pore foams fabricated by the mechanical mixing of hollow glass particles in a matrix resin. The present study deals with change in compressive properties of syntactic foams due to the incorporation of nano-sized clay (nanoclay) particles. A surface modified clay, Nanomer I.30E, has been used in the fabrication of specimens. Six different types of syntactic foams are fabricated and tested for compressive properties. Three types of hollow particles (microballoons) of glass having diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 16 publications
1
42
0
Order By: Relevance
“…reported the effect of nanoclay in syntactic foam [9,10]. However, these studies focus on quasi-static behavior.…”
Section: Introductionmentioning
confidence: 97%
“…reported the effect of nanoclay in syntactic foam [9,10]. However, these studies focus on quasi-static behavior.…”
Section: Introductionmentioning
confidence: 97%
“…It is also known that modulus, toughness and thermo mechanical properties of epoxy resin can be significantly enhanced by the addition of nanoclay [14][15][16][17][18][19]. Gupta and Maharsia [20] observed 80% and 125% increase in toughness, measured as area under the stress strain curves, for 2% and 5% nanoclay, respectively, in syntactic foam containing microballoons of density 220 kg/cm 3 . However, they observed a decrease in compressive strength by 10-20% by the incorporation of 2 vol% nanoclay, whereas 5% nanoclay has given nearly same level of strength.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to the reinforcing effect of the nanoclay particles which improve the load bearing ability of the foam composites. Gupta and Maharsia also observed an improvement in compressive properties of epoxy syntactic foams with the addition of 5% nanoclay, whereas for the 2% nanoclay system, the compressive strength is lower than that for plain syntactic foam [7].…”
Section: Mechanical Propertiesmentioning
confidence: 89%
“…In nanoclay syntactic foams, flexural strength was observed to depend on the nanoclay volume fraction [6]. Gupta and Maharsia found that the toughness has improved by 80-200% by nanoclay reinforcement [7]. Maharsia et al claimed an increase in tensile strength upon the addition of nanoclay particles.…”
Section: Introductionmentioning
confidence: 97%